2021
DOI: 10.3390/horticulturae7120555
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals, Antioxidant and Antidiabetic Activities of Extracts from Miliusa velutina Flowers

Abstract: The flowers of M. velutina were extracted with ethanol to obtain a crude extract that was consecutively extracted using n-hexane, dichloromethane, ethyl acetate and water. The crude extract and fractions were studied for the chemical composition and antioxidant and antidiabetic activities. The extracts had various phytoconstituents, namely steroids, flavonoids, tannins, saponins, alkaloids and glycosides. The aqueous extract had the highest total polyphenol (12.6 mg GAE/g extract) and total flavonoid (205.6 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
3
3
0
1
Order By: Relevance
“…However, the lower amount of phenolic was observed when compared to that of total flavonoids in this study. The similar result could be previously observed and explained by Anh et al. (2021) .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, the lower amount of phenolic was observed when compared to that of total flavonoids in this study. The similar result could be previously observed and explained by Anh et al. (2021) .…”
Section: Resultssupporting
confidence: 92%
“…Many published studies have suggested that the antioxidant activity of plant extracts is related to their antidiabetic activities and antiglycation activity. As demonstrated by Anh's research, the extracts from Miliusa velutna flowers showed a positive correlation between their antioxidant activity and their capacities to inhibit the carbohydrate digestive enzymes (α-amylase and α-glucosidase) ( Anh et al., 2021 ). In addition, some edible and medicinal plants have high antioxidant activity, exhibited strong antiglycation activity ( Kaewnarin et al., 2014 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…EAF showed the highest phenolic content while favonoid content was higher in DMF. Te results are in agreement with the previously reported studies [43,44].…”
Section: Discussionsupporting
confidence: 93%
“…Trong các thử nghiệm kháng oxy hóa ở trên, tinh chất trolox được sử dụng làm đối chứng dương. Các hoạt động kháng oxy hóa của cao tối ưu LXĐ được so sánh với hoạt tính của trolox và cao LXĐ (cao LXĐ là cao được chiết xuất trong điều kiện bình thường theo mô tả của Phụng (2007) và Anh et al (2021), cụ thể như sau: ethanol 99,5% (v/v), nhiệt độ chiết 30 ○ C, thời gian 24 giờ và tỷ lệ nguyên liệu/ dung môi là 1/10 (w/v)) bằng cách tính toán nồng độ (µg/mL) mà cao tối ưu LXĐ, cao LXĐ hoặc trolox có thể khử hoặc trung hòa 50% các gốc tự do (effective concentration of 50%, EC 50 ).…”
Section: Khảo Sát Hoạt Tính Kháng Oxy Hóa Và Kháng đTđ In Vitro Khả...unclassified